Análise dos recursos hídricos, do saneamento básico e das doenças de veiculação hídrica nos bairros Paracurí e Águas Negras em Belém /PA - Melo, André Veloso de (2014)
This study aims to analyze the conditions of water resources; sanitation and occurrence of waterborne diseases in districts of Águas Negras and Paracuri in Belém do Pará. As part of this study, the literature survey was conducted to benchmark theoretical, the Geography of Health, the importance of water resources for humans, sanitation of waterborne and location of the study area diseases. For the preparation of statistical data relating to sanitation and waterborne diseases in Brazil, in the state of Pará in Belém and information from official bodies such as the Brazilian Institute of Geography and Statistics (IBGE), Ministry of Health and were collected Department of Public Health (SESPA). The application of fifty questionnaires found that the socio economic, sanitation and waterborne diseases conditions, with residents was also conducted. It is concluded that the basic sanitation in Brazil is still very poor, especially in the North and Northeast; it directly influences the number of notifications of waterborne diseases in the country. In the neighborhoods of Paracuri and blackwater, by analyzing the interviews that there is a lack of sewage collection and treatment, regular water connections incidence of waterborne diseases causing large number of hospitalizations